Method capable of preparing three-function electrocatalyst with oxygen reduction, oxygen evolution and hydrogen evolution on large scale, product and application of three-function electrocatalyst

Through the method of combining high-energy ball milling and pyrolysis, a nitrogen-doped graphite-supported cobalt nanoparticle composite material was prepared, solving the problems of limited resources and high cost of existing precious metal electrocatalysts, and achieving efficient, stable and large-scale production of three-function electrocatalysts of oxygen reduction, oxygen precipitation and hydrogen precipitation.

CN119615248AActive Publication Date: 2025-03-14HUNAN UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411773279.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing electrocatalysts for oxygen reduction, oxygen precipitation and hydrogen precipitation reactions mainly rely on precious metals such as platinum, with limited resources and high costs, making it difficult to achieve large-scale production and wide application.

Method used

Using a method of combining high-energy ball milling and pyrolysis, expandable graphite is used as the basic raw material to prepare cobalt nanoparticle composite materials supported by nitrogen-doped graphite to achieve efficient preparation of three-function electrocatalysts of oxygen reduction, oxygen precipitation and hydrogen precipitation.

Benefits of technology

This method simplifies the preparation process and is easy to produce on a large scale. The catalyst exhibits excellent electrocatalytic activity and high stability for oxygen reduction, oxygen precipitation and hydrogen precipitation reactions, reducing costs and is of great practical significance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615248A_ABST
    Figure CN119615248A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an electrocatalyst with three functions of oxygen reduction, oxygen evolution and hydrogen evolution on a large scale, which comprises the following steps: firstly, oxidizing graphite to obtain expandable graphite powder of which the specific surface area is greatly increased; then, the expandable graphite powder and ammonium carbonate are mixed and subjected to high-energy ball milling treatment, ammonium carbonate serves as an intercalator to further weaken the acting force between graphite in the ball milling process, ethylene glycol serves as a grinding agent, and a large amount of fragment-shaped graphite is generated through ball milling treatment; then, the added cobalt phthalocyanine continues to be subjected to ball milling to be damaged into small fragments, and the small fragments are fixed to the surface of the fragment-shaped graphite; and after dicyandiamide is added, high-temperature pyrolysis treatment is carried out, and the nitrogen-doped graphite-loaded and carbon-nitrogen-compound-coated cobalt nanoparticle compound is obtained. The compound has excellent electrocatalytic activity and stability on oxygen reduction, oxygen evolution and hydrogen evolution at the same time. The preparation process of the compound is simple, large-scale production is easy to realize, and the compound has important practical significance in the fields of electrochemical new energy and water electrolysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of water electrolysis and electrochemical energy materials, and specifically provides a method for scalably preparing a trifunctional electrocatalyst of oxygen reduction-oxygen evolution-hydrogen evolution, and a product and application thereof. Background Art

[0002] The development of new electrocatalysts for oxygen reduction, oxygen evolution and hydrogen evolution reactions has important practical significance for the research of electrochemical new energy and water electrolysis. Oxygen reduction reaction is an indispensable cathode process in electrochemical new energy such as fuel cells and metal-air batteries. The development of corresponding efficient electrocatalysts is of great significance for the practical application of such electrochemical new energy. At present, platinum or platinum-based catalysts are the most effective electrocatalysts for oxygen reduction reaction, but the limited resources and high cost of platinum seriously restrict their practical application in electrochemical new energy. Similarly, for the water electrolysis process, both oxygen evolution at the anode and hydrogen evolution at the cathode require efficient electrocatalysts. Under the current circumstances, platinum or platinum-based catalysts are also the most efficient electrocatalysts for hydrogen evolution; for oxygen evolution, iridium oxide is also an efficient electrocatalyst. In short, for oxygen reduction, oxygen evolution and hydrogen evolution reactions, the current effective electrocatalysts are still precious metal materials, so the development of non-precious metal electrocatalysts is of great practical significance for the wide application of new electrochemical energy and water electrolysis.

[0003] In order to develop non-precious metal electrocatalysts, people have conducted a lot of research and proposed various preparation methods. But in general, since these electrocatalysts are in the form of nanoparticle dispersion, their preparation process is usually cumbersome, which makes it difficult to mass-produce them. Therefore, the development of non-precious metal electrocatalysts with simple preparation process, easy industrial-scale application, and high-efficiency electrocatalytic activity has a practical effect on the large-scale practical application of new electrochemical energy and electrolysis of water. The present invention uses expandable graphite with a large specific surface area as the basic raw material, and adopts a simple method combining high-energy ball milling with a pyrolysis process to prepare nitrogen-doped graphite-loaded cobalt nanoparticle composite materials, which show excellent electrocatalytic activity and high stability for oxygen reduction, oxygen precipitation and hydrogen precipitation. The process of the present invention is simple and easy to achieve large-scale production. Summary of the invention

[0004] The purpose of the present invention is to provide a method for scalably preparing a trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution, and a product and application thereof.

[0005] To achieve the above object, the embodiment of the present invention is: a method for scalably preparing a trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution, comprising the following steps:

[0006] (1) adding graphite to concentrated sulfuric acid, stirring evenly, then adding 60% hydrogen peroxide, stirring the mixture evenly, placing it in a 40° C. constant temperature water bath, letting it stand, and after sufficient reaction, filtering and washing with water until the pH value is 5 to 6, and drying the obtained solid at 50° C., and then grinding it thoroughly to obtain expanded graphite powder;

[0007] (2) The expandable graphite powder and ammonium carbonate are mixed at a mass ratio of 1:20, and then an appropriate amount of ethylene glycol is added to ensure that the ethylene glycol completely immerses the solid mixture, and then sufficient ball milling is performed, and then cobalt phthalocyanine is added and the ball milling is continued to be sufficient. The obtained mixed solid is a ball milling product containing ethylene glycol; the ball milling product is mixed with an appropriate amount of anhydrous ethanol, stirred evenly and then allowed to stand, and then the upper ethanol solution is poured out, and the obtained solid is repeatedly treated with anhydrous ethanol to obtain Precursor-1;

[0008] The mass ratio of the cobalt phthalocyanine to the expandable graphite powder is 1:2; the total mass of the agate balls used in the ball milling process is 10 to 15 times the mass of ammonium carbonate;

[0009] (3) Precursor-1 and dicyandiamide are mixed at a mass ratio of 1:(0.5-5), and then an appropriate amount of anhydrous ethanol is added, and the mixture is fully ground and dried at 40° C., and then fully ground again to obtain Precursor-2;

[0010] (4) The above-mentioned precursor-2 was heated at 4°C min in a nitrogen atmosphere. -1 The catalyst was heated to 152°C and maintained for 0.5 h, then continued to be heated to 800°C and maintained for 2 h. After cooling to room temperature, the obtained solid was collected and fully ground to obtain a trifunctional electrocatalyst of oxygen reduction-oxygen evolution-hydrogen evolution.

[0011] A scalable trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution prepared according to the method described.

[0012] A scalable trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution prepared by the method is used in oxygen reduction, oxygen evolution and hydrogen evolution.

[0013] The present invention firstly performs an oxidation treatment on graphite to obtain expandable graphite powder with a greatly increased specific surface area; then the expandable graphite powder is mixed with ammonium carbonate and subjected to high-energy ball milling treatment. Ammonium carbonate, as an intercalating agent, further weakens the interaction between graphites during the ball milling process. With ethylene glycol as an abrasive, the ball milling treatment produces a large amount of fragmented graphite; the cobalt phthalocyanine added thereafter is further broken into small fragments after ball milling and fixed on the surface of the fragmented graphite; after adding dicyandiamide, a high-temperature pyrolysis treatment is performed to obtain a nitrogen-doped graphite-loaded cobalt nanoparticle complex coated with a carbon-nitrogen complex. This complex has excellent electrocatalytic activity and stability for oxygen reduction, oxygen precipitation and hydrogen precipitation at the same time. The preparation process of this complex of the present invention is simple, and it is easy to realize large-scale production, and it has important practical significance in the fields of electrochemical new energy and water electrolysis. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Schematic diagram of the preparation mechanism of the catalyst product;

[0015] Figure 2 This is a SEM image of the catalyst product prepared in Example 1;

[0016] Figure 3 This is the SEM image of the catalyst product prepared in Example 2.

[0017] Figure 4 The electrocatalytic activity diagram of the catalyst product prepared in Example 1 for oxygen reduction (ORR), oxygen evolution (OER) and hydrogen evolution (HER).

[0018] Figure 5 The electrocatalytic activity diagram of the catalyst product prepared in Example 2 for oxygen reduction (ORR), oxygen evolution (OER) and hydrogen evolution (HER). DETAILED DESCRIPTION

[0019] Example 1

[0020] A method for scalably preparing a trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution comprises the following steps:

[0021] (1) According to the prior art (Zhao Guogang, Ma Jiyang, Wu Yan, Preparation of expandable graphite by hydrogen peroxide oxidation, Journal of Heilongjiang University of Science and Technology, 2014, 24 (2): 173-176), expandable graphite powder was prepared, and the specific steps were as follows: 10 g of graphite was added to 28 mL of concentrated sulfuric acid, stirred evenly, and then 1 mL of 60% hydrogen peroxide was added. After the mixture was fully stirred until uniform, stirring was stopped, and the mixture was placed in a 40° C. constant temperature water bath and allowed to stand for 1 hour. After the reaction was completed, the mixture was filtered and washed with water until the pH was 5-6. The obtained solid was dried at 50° C. for 4 hours, and then fully ground to obtain expandable graphite powder.

[0022] (2) 0.2 g of expandable graphite powder and 4 g of ammonium carbonate were mixed and transferred to a high-energy ball mill, and then an appropriate amount of ethylene glycol was added to ensure that the ethylene glycol completely submerged the solid mixture; a small agate ball with a diameter of 5 mm was added, and the mixture was ball milled at a speed of 500 rpm for 8 hours, and then 0.4 g of cobalt phthalocyanine was added to the ball mill, and the high-energy ball milling treatment was continued for 8 hours. The obtained mixed solid was a ball milling product containing ethylene glycol. The ball milling product was mixed with an appropriate amount of anhydrous ethanol, stirred evenly, and then allowed to stand. The upper ethanol solution was then poured out, and the obtained solid was repeatedly treated with anhydrous ethanol once, and finally Precursor-1 was obtained.

[0023] (3) The above-mentioned precursor-1 was mixed with 2 g of dicyandiamide, and then an appropriate amount of anhydrous ethanol was added, and the mixture was thoroughly ground in a mortar. The resulting mixture was dried at 40° C. for 6 hours; then, the mixture was thoroughly ground to obtain precursor-2.

[0024] (4) The above-mentioned precursor-2 was transferred to a tube furnace and heated at 4°C min under a nitrogen atmosphere. -1 The mixture was heated to 152°C at a rate of 100 °C and maintained for 0.5 h, and then continued to be heated to 800°C and maintained for 2 h. After cooling to room temperature, the obtained solid was collected and fully ground to obtain a catalyst product.

[0025] (5) The above catalyst product was mixed with an appropriate amount of ethanol, and then Nafion solution was added. The slurry formed after ultrasonic mixing was coated on the surface of the hydrophobic treated carbon cloth. After drying, an air electrode was obtained. It was used as a working electrode and a carbon rod as a counter electrode and a HgO / Hg electrode as a reference electrode to form a three-electrode system. The polarization curves of hydrogen evolution (HER) and oxygen evolution (OER) reactions were tested in 1M KOH solution, and the polarization curve of oxygen reduction reaction (ORR) was tested in 0.1M KOH solution. For comparison, the polarization curves of hydrogen evolution (HER) of Pt / C catalyst and oxygen evolution (OER) of IrO2 catalyst in 1M KOH solution were tested; the polarization curve of oxygen reduction reaction (ORR) of Pt / C catalyst in 0.1M KOH solution was tested. At 10mA / cm 2 At the current density of 50 mA / cm, the difference ΔV between the potential corresponding to OER and the potential corresponding to HER is: ΔV = 1.76 V (catalyst product), ΔV = 1.70 V (Pt / C / IrO2 system); 2 At the current density of 10 mA / cm2, the difference ΔV between the potential corresponding to OER and the potential corresponding to HER is: ΔV = 1.98 V (catalyst product), ΔV = 1.98 V (Pt / C / IrO2 system). 2The difference ΔE between the potential corresponding to OER and the half-wave potential of ORR at the current density is: ΔE=0.76V (catalyst product), ΔE=0.59V (Pt / C / IrO2 system).

[0026] Example 2

[0027] A method for scalably preparing a trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution comprises the following steps:

[0028] (1) According to the prior art (Zhao Guogang, Ma Jiyang, Wu Yan, Preparation of expandable graphite by hydrogen peroxide oxidation, Journal of Heilongjiang University of Science and Technology, 2014, 24 (2): 173-176), expandable graphite powder was prepared, and the specific steps were as follows: 10 g of graphite was added to 28 mL of concentrated sulfuric acid, stirred evenly, and then 1 mL of 60% hydrogen peroxide was added. After the mixture was fully stirred until uniform, stirring was stopped, and the mixture was placed in a 40° C. constant temperature water bath and allowed to stand for 1 hour. After the reaction was completed, the mixture was filtered and washed with water until the pH was 5-6. The obtained solid was dried at 50° C. for 4 hours, and then fully ground to obtain expandable graphite powder.

[0029] (2) 0.2 g of expandable graphite powder and 4 g of ammonium carbonate were mixed and transferred to a high-energy ball mill, and then an appropriate amount of ethylene glycol was added to ensure that the ethylene glycol completely submerged the solid mixture; a small agate ball with a diameter of 5 mm was added, and the mixture was ball milled at a speed of 500 rpm for 8 hours, and then 0.4 g of cobalt phthalocyanine was added to the ball mill, and the high-energy ball milling treatment was continued for 8 hours. The obtained mixed solid was a ball milling product containing ethylene glycol. The ball milling product was mixed with an appropriate amount of anhydrous ethanol, stirred evenly, and then allowed to stand. The upper ethanol solution was then poured out, and the obtained solid was repeatedly treated with anhydrous ethanol once, and finally Precursor-1 was obtained.

[0030] (3) The above-mentioned precursor-1 was mixed with 4 g of dicyandiamide, and then an appropriate amount of anhydrous ethanol was added, and the mixture was thoroughly ground in a mortar. The resulting mixture was dried at 40° C. for 6 hours; then, the mixture was thoroughly ground to obtain precursor-2.

[0031] (4) The above-mentioned precursor-2 was transferred to a tube furnace and heated at 4°C min under a nitrogen atmosphere. -1 The mixture was heated to 152°C at a rate of 100 °C and maintained for 0.5 h, and then continued to be heated to 800°C and maintained for 2 h. After cooling to room temperature, the obtained solid was collected and fully ground to obtain a catalyst product.

[0032] (5) The above catalyst product was mixed with an appropriate amount of ethanol, and then Nafion solution was added. The slurry formed after ultrasonic mixing was coated on the surface of the hydrophobic treated carbon cloth. After drying, an air electrode was obtained. It was used as a working electrode and a carbon rod as a counter electrode and a HgO / Hg electrode as a reference electrode to form a three-electrode system. The polarization curves of hydrogen evolution (HER) and oxygen evolution (OER) reactions were tested in 1M KOH solution, and the polarization curve of oxygen reduction reaction (ORR) was tested in 0.1M KOH solution. For comparison, the polarization curves of hydrogen evolution (HER) of Pt / C catalyst and oxygen evolution (OER) of IrO2 catalyst in 1M KOH solution were tested; the polarization curve of oxygen reduction reaction (ORR) of Pt / C catalyst in 0.1M KOH solution was tested. At 10mA / cm 2 At the current density of 50 mA / cm, the difference ΔV between the potential corresponding to OER and the potential corresponding to HER is: ΔV = 1.79 V (catalyst product), ΔV = 1.70 V (Pt / C / IrO2 system); 2 At the current density of 10 mA / cm2, the difference ΔV between the potential corresponding to OER and the potential corresponding to HER is: ΔV = 1.95 V (catalyst product), ΔV = 1.98 V (Pt / C / IrO2 system). 2 The difference ΔE between the potential corresponding to OER and the half-wave potential of ORR at the current density is: ΔE=0.763V (catalyst product), ΔE=0.59V (Pt / C / IrO2 system).

Claims

1. A method for scalably preparing a trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution, characterized in that: The following steps are involved: (1) adding graphite to concentrated sulfuric acid, stirring evenly, then adding 60% hydrogen peroxide, stirring the mixture evenly, placing it in a 40° C. constant temperature water bath, letting it stand, and after sufficient reaction, filtering and washing with water until the pH value is 5 to 6, and drying the obtained solid at 50° C., and then grinding it thoroughly to obtain expanded graphite powder; (2) The expandable graphite powder and ammonium carbonate are mixed at a mass ratio of 1:20, and then an appropriate amount of ethylene glycol is added to ensure that the ethylene glycol completely immerses the solid mixture, and then sufficient ball milling is performed, and then cobalt phthalocyanine is added and the ball milling is continued to be sufficient. The obtained mixed solid is a ball milling product containing ethylene glycol; the ball milling product is mixed with an appropriate amount of anhydrous ethanol, stirred evenly and then allowed to stand, and then the upper ethanol solution is poured out, and the obtained solid is repeatedly treated with anhydrous ethanol to obtain Precursor-1; The mass ratio of the cobalt phthalocyanine to the expandable graphite powder is 1:2; the total mass of the agate balls used in the ball milling process is 10 to 15 times the mass of ammonium carbonate; (3) Precursor-1 and dicyandiamide are mixed at a mass ratio of 1:(0.5-5), and then an appropriate amount of anhydrous ethanol is added, and the mixture is fully ground and dried at 40° C., and then fully ground again to obtain Precursor-2; (4) The above-mentioned precursor-2 was heated at 4°C min in a nitrogen atmosphere. -1 The catalyst was heated to 152°C and maintained at this temperature for 0.5 h, and then continued to be heated to 800°C and maintained at this temperature for 2 h. After cooling to room temperature, the obtained solid was collected and ground thoroughly to obtain a trifunctional electrocatalyst of oxygen reduction-oxygen evolution-hydrogen evolution.

2. A scalable trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution prepared according to the method of claim 1.

3. Application of a scalable trifunctional electrocatalyst for oxygen reduction-oxygen evolution-hydrogen evolution prepared by the method of claim 1 in oxygen reduction, oxygen evolution and hydrogen evolution.

Citation Information

Patent Citations

  • Preparation method of high flame retardant expansible graphite

    CN101786618A

  • N-doped carbon-loaded double-scaling transition metal phosphide and preparation method and application thereof

    CN108517537A

  • Electrochemical production of graphene sheets from coke or coal

    CN109328104A

  • Preparation, product and application of nitrogen-cobalt-phosphorus co-doped carbon hollow sphere composite material

    CN110635144A

  • Universal preparation and application of nitrogen-rich graphene aerogel loaded monatomic cluster catalyst based on sol-gel method

    CN111744522A